2022
DOI: 10.21203/rs.3.rs-2085125/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Practice, and factors associated with neonatal pain management among nurses working at West Oromia Public Hospitals, Ethiopia: A cross-sectional study

Abstract: Introduction: Pain is an unpleasant sensory and emotional experience associated with actual or potential damage. Recently, in developing countries including Ethiopia, there is insufficient data regarding the knowledge and practice of neonatal pain management among nurses. Hence, the current study identified the nurses’ knowledge, practice, and factors associated with neonatal pain management at west Oromia public hospitals. Objective This study aimed to assess knowledge, practice, and factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…Consequently, pain tends to be overlooked in this particular population. These findings align with studies conducted in Ethiopia, specifically in Addis Ababa and western Oromia [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consequently, pain tends to be overlooked in this particular population. These findings align with studies conducted in Ethiopia, specifically in Addis Ababa and western Oromia [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Adequate education likely provides professionals with a solid foundation of knowledge and skills necessary for effective pain management in neonates. This finding aligns with a study conducted in Addis Ababa and West Oromia, where a positive association was identified between having adequate knowledge and better neonatal pain management knowledge [ 13 ]. The consistent pattern across studies underscores the importance of education as a key determinant in promoting proficiency and expertise in neonatal pain management among health care professionals.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations